EXPLORING PRE-SERVICE TEACHERS’ BELIEFS ABOUT THE ROLE OF ARTIFICIAL INTELLIGENCE IN HIGHER EDUCATION IN GHANA - Butakor, Paul Kwame (International Journal of Innovative Technologies in Social Science, 2023)
The role of Artificial Intelligence (AI) in education has been well-documented in developed societies. However, the phenomenon has received little attention in developing countries such as Ghana. This study examined pre-service teachers from one of the teacher education universities in Ghana beliefs about the role of artificial intelligence in higher education. This study employed the quantitative descriptive design to obtain data from a convenience sample of 231 pre-service teachers. The study revealed that the majority of the pre-service teachers are very much aware of AI systems and that using AI-related systems will have a positive effect on pre-service teachers’ performance and that AI has the potential to replace teacher’s absence. Further, the majority of the respondents indicated that AI is relevant as it provides new ways of attaining distinction in teaching and learning. On the contrary, it was discovered that the majority of the pre-service teachers indicated that they feel anxious when it comes to using AI-related systems in learning. It is therefore recommended that more training and support systems be put in place to help and support pre-service teachers when using AI systems during teaching and learning during the post-pandemic era.